Analysis of the Application of Value Added Tax on Port Services based on Law Number 7 of 2021 at PT Kaltim Kariangau Terminal, East Kalimantan - Monica Omega Torba; Inggriani Elim; Anneke Wangkar (Formosa Journal of Applied Sciences, 2023)
Value Added Tax (VAT) is a tax levy imposed on sales and purchase transactions of taxable goods or services carried out by Individual Taxpayers and Corporate Taxpayers who have been confirmed as Taxable Entrepreneurs (PKP). This research aims to find out that the implementation of Value Added Tax in companies is in accordance with Law Number 7 of 2021. The research method used in this research is a descriptive method with a qualitative approach and data is obtained through interviews and documentation. The research results show that the implementation of Value Added Tax at PT Kaltim Kariangau Terminal is in accordance with Law Number 7 of 2021. .